Sequence analysis of pLBB1, a cryptic plasmid from Lactobacillus delbrueckii subsp. bulgaricus - Azcárate Peril, María Andrea (2002)
The first report of the complete nucleotide sequence of a cryptic plasmid from Lactobacillus delbrueckii subsp. bulgaricus (Lactobacillus bulgaricus) is presented. The plasmid pLBB1 consists of 6127 bp with a GC content of 44.8%. No ssDNA was detected by hybridization experiments, which is consistent with the notion that pLBB1 does not replicate by a rolling circle mechanism. A putative replication region of pLBB1 was cloned and found to be functional in Lactobacillus johnsonii and Lactococcus lactis. Plasmid pLBB1 showed significant DNA sequence identity with plasmid pLL1212 from Lactobacillus delbrueckii subsp. lactis (Lactobacillus lactis) CRL1212 (GenBank accession No. AF109691). Four open reading frames (ORFs) larger than 100 amino acids were identified. ORFA shared similarity with a putative primase-helicase system, and ORFB and ORFC exhibited limited identity with a mobilization protein and a transposase, respectively. Curing experiments did not allowed us to assign a function to the ORFs.